Animal-in-the-loop system to investigate adaptive behavior. (2nd September 2018) - Shigaki, S.; Fikri, M. R.; Hernandez Reyes, C.; Sakurai, T.; Ando, N.; Kurabayashi, D.; Kanzaki, R.; Sezutsu, H.
ABSTRACT: In this research, we aim to model an adaptive behavior of an animal and implement it to an autonomous robot. The conventional bio-inspired algorithm is difficult to demonstrate the ability as much as the animal because it models without considering dynamic characteristics of the robot. Therefore, in this study, we constructed an animal-in-the-loop system, which is a novel experimental system for identifying the adaptive behavior of the animal in a form that considers the dynamic characteristics of the robot to be implemented. GRAPHICAL ABSTRACT: